Stripe phases in WSe2/WS2 moiré superlattices - Jin, Chenhao; Tao, Zui; Li, Tingxin; Xu, Yang; Tang, Yanhao; Zhu, Jiacheng; Liu, Song; Watanabe, Kenji; Taniguchi, Takashi; Hone, James C.; Fu, Liang; Shan, Jie; et al. (Nature materials, 2021)
Stripe phases, in which the rotational symmetry of charge density is spontaneously broken, occur in many strongly correlated systems with competing interactions 1 – 11 . However, identifying and studying such stripe phases remains challenging. Here we uncover stripe phases in WSe 2 /WS 2 moiré superlattices by combining optical anisotropy and electronic compressibility measurements. We find strong electronic anisotropy over a large doping range peaked at 1/2 filling of the moiré superlattice. The 1/2 state is incompressible and assigned to an insulating stripe crystal phase. Wide-field imaging reveals domain configurations with a preferential alignment along the high-symmetry axes of the moiré superlattice. Away from 1/2 filling, we observe additional stripe crystals at commensurate filling 1/4, 2/5 and 3/5, and compressible electronic liquid crystal states at incommensurate fillings. Our results demonstrate that two-dimensional semiconductor moiré superlattices are a highly tunable platform from which to study the stripe phases and their interplay with other symmetry breaking ground states. Optical anisotropy and electronic compressibility measurements are used to uncover stripe phases, where the rotational symmetry of charge density is spontaneously broken, in a two-dimensional semiconductor moiré superlattice.